Relationship between age at initiation of cysteamine treatment, adherence with therapy, and glomerular kidney function in infantile nephropathic cystinosis - Nießl, Christina; Boulesteix, Anne-Laure; Oh, Jun; Palm, Katja; Schlingmann, Peter; Wygoda, Simone; Haffner, Dieter; Wühl, Elke; Tönshoff, Burkhard; Büscher, Anja K.; Billing, Heiko; Hoppe, Bernd; et al. (Molecular genetics and metabolism, 2022)
Infantile nephropathic cystinosis, due to impaired transport of cystine out of lysosomes, occurs with an incidence of 1 in 100-200,000 live births. It is characterized by renal Fanconi syndrome in the first year of life and glomerular dysfunction progression to end-stage kidney disease by approximately 10 years of age. Treatment with oral cysteamine therapy helps preserve glomerular function, but affected individuals eventually require kidney replacement therapy.
Gesehen am 04.10.2021